Adsorption and Release of Sulfamethizole from Mesoporous Silica Nanoparticles Functionalised with Triethylenetetramine - Cristina Carucci (International Journal of Molecular Sciences, 2021)
Mesoporous silica nanoparticles (MSN) were synthesised and functionalised with triethylenetetramine (MSN-TETA). The samples were fully characterised (transmission electron microscopy, small angle X-ray scattering, Fourier transform infrared spectroscopy, thermogravimetric analysis, zeta potential and nitrogen adsorption/desorption isotherms) and used as carriers for the adsorption of the antimicrobial drug sulphamethizole (SMZ). SMZ loading, quantified by UV–Vis spectroscopy, was higher on MSN-TETA (345.8 mg g−1) compared with bare MSN (215.4 mg g−1) even in the presence of a lower surface area (671 vs. 942 m2 g−1). The kinetics of SMZ adsorption on MSN and MSN-TETA followed a pseudo-second-order model. The adsorption isotherm is described better by a Langmuir model rather than a Temkin or Freundlich model. Release kinetics showed a burst release of SMZ from bare MSN samples (k1 = 136 h−1) in contrast to a slower release found with MSN-TETA (k1 = 3.04 h−1), suggesting attractive intermolecular interactions slow down SMZ release from MSN-TETA. In summary, the MSN surface area did not influence SMZ adsorption and release. On the contrary, the design of an effective drug delivery system must consider the intermolecular interactions between the adsorbent and the adsorbate.